Gas station emissions: risk assessment in the context of ensuring sustainable development - Karaim, O. A.; Bakaraiev, O. A.; Karaim, V. P.; Lavrynyuk, Z. V. (Man and Environment. Issues of Neoecology, 2025)
Purpose. To carry out an inventory of pollutant emissions generated by the operation of a filling station and to assess the total non-carcinogenic risk in the context of ensuring sustainable development. Methods. Experimental and analytical methods, as well as mathematical modeling and forecasting techniques. Results. An analysis of atmospheric emissions from a filling station located in the Lutsk district of the Volyn region was conducted. The sources of pollutant formation at the facility include underground steel horizontal cylindrical tanks for gasoline and diesel fuel storage, double-sided fuel dispensers, above-ground steel tanks for liquefied petroleum gas, and a gas-filling dispenser. Maximum one-time and annual emissions were determined using instrumental measurements, analytical calculations, design data, and technological standards. According to the total annual volume of emissions, the facility belongs to the third category. The operation of the filling station results in the release of hydrogen sulfide, saturated hydrocarbons, benzene, xylene, toluene, propane, and butane into the atmospheric air. The calculated ground-level concentrations of pollutants, including background pollution, at the boundary of the sanitary protection zone and residential areas do not exceed hygienic standards. The hazard index values for the four control points correspond to a warning level of total non-carcinogenic risk. The identified level of risk requires further monitoring and the implementation of emission-reduction measures, which is an essential prerequisite for ensuring sustainable development. Conclusions. Pollutant concentrations at the boundary of the sanitary protection zone do not exceed regulatory limits. However, the warning level of total non-carcinogenic risk necessitates continued monitoring, assessment of potential health impacts, and the implementation of effective environmental protection measures. Reducing emissions is a critical condition for the safe operation of the filling station and for supporting the sustainable development of the surrounding area.